2011
DOI: 10.1371/journal.pntd.0001029
|View full text |Cite
|
Sign up to set email alerts
|

Recent Food Shortage Is Associated with Leprosy Disease in Bangladesh: A Case-Control Study

Abstract: BackgroundLeprosy is remaining prevalent in the poorest areas of the world. Intensive control programmes with multidrug therapy (MDT) reduced the number of registered cases in these areas, but transmission of Mycobacterium leprae continues in most endemic countries. Socio-economic circumstances are considered to be a major determinant, but uncertainty exists regarding the association between leprosy and poverty. We assessed the association between different socio-economic factors and the risk of acquiring clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 16 publications
4
63
1
5
Order By: Relevance
“…3,8 Tal fato é corroborado ao analisar a distribuição espacial da hanseníase no mundo. Em países desenvolvidos, poucos novos casos são registrados e, quando detectados, são encontrados principalmente entre os imigrantes de países onde a doença ainda é endêmica.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…3,8 Tal fato é corroborado ao analisar a distribuição espacial da hanseníase no mundo. Em países desenvolvidos, poucos novos casos são registrados e, quando detectados, são encontrados principalmente entre os imigrantes de países onde a doença ainda é endêmica.…”
Section: Discussionunclassified
“…6 Há muito se discute que as condições de alto risco para a distribuição e propagação da endemia hansênica são, em sua maioria, relacionadas à pobreza. 7 Altas taxas de desnutrição, 8 aglomeração domiciliar 9 e baixa escolaridade 10 são alguns dos fatores já identificados.…”
Section: Introductionunclassified
“…Income inequality is inversely associated to health status (Wilkinson & Pickett 2006). In Brazil, inequality is engrained in the differences across regions and educational levels (Salardi 2005), labour market segmentation, and discrimination against women and non-White people (Lustig & Lopez-Calva 2013 cultural factors (Skidmore 2004 (Feenstra et al 2011). Urbanity, inequality, great number of dwellers by residence and migration are all closely interrelated.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the circumstances, most of the data are anecdotal and are not derived from well-designed studies [6]. In line with these observations, a case-control study in Bangladesh reported an association between the occurrence of leprosy and a period of food shortage [7]. …”
Section: Impact Of Nutritional Status On Infectionsmentioning
confidence: 99%